Three-dimensional analysis of hydraulic effect on unsaturated slope stability. Issue 1 (30th April 2014) - Arairo, Wahib; Prunier, Florent; Djeran-Maigre, Irini; Millard, Alain
Abstract : A novel approach developed by the authors to predict the behaviour of unsaturated soils is discussed in this paper to investigate the effect of rainfall event on the stability of soil slopes. Heavy rainfall is one of the main factors that induce shallow landslides. This type of landslide usually takes place in partial saturated slopes. Numerical models taking into account the key physical processes that unsaturated soils undergo during different phases of rainfall events could help in the understanding of the main sliding mechanisms. The contribution of partially saturated soils and matric suction, as well as the change in hydraulic conductivity due to rainfall, should be taken into account to well represent the complete effect of seepage. In this paper, an elastoplastic constitutive model that captures the main features of the behaviour of unsaturated soils is used in a fully coupled hydromechanical, three-dimensional, finite-element analysis, catching the destabilising processes in a steep slope during rain infiltration.